List of documents, 1951-1982. - World Health Organization. (Regional Office for Europe, World Health Organization ; WHO Publications Centre, USA [distributor], 1983)
Contains a list of publications produced by WHO and its regional offices from 1951 to 1982
Contains a list of publications produced by WHO and its regional offices from 1951 to 1982
Keywords: Public Health.; Public health / Europe / Bibliography / Catalogs.; Public health / Bibliography / Catalogs.; Europe.; Catalogs.; Bibliography.